Critical Thinking, Metacognition, and Dual-Process Theory - Nadurak, Vitaliy (Informal Logic, 2026)
In this article, critical thinking is interpreted as a type of metacognition aimed at evaluating thinking for compliance with standards of rationality. The author argues that dual-process theory provides a strong theoretical foundation for explaining critical thinking, as it reflects its fundamental idea, explains why it is necessary, and accounts for why people do not always think critically. The article also contends that critical thinking should not be equated exclusively with deliberate thinking and examines its intuitive components, showing that certain aspects of critical thinking can occur automatically.